Metodologi Mazhab Zahiri Dalam Pemahaman Nash: Analisis Terhadap Kesempurnaan Rakaat Sholat - Andi Mustopa; Muhamad Syaikhu; Bakhtiar; Jamaluddin Acmad Kholik (Indonesian Journal of Islamic Theology and Philosophy, 2025)
Abstract This study analyzes the methodological principles of the Zahiri school of thought in determining the perfection of prayer rak'ahs, focusing on their literalist approach to understanding the texts. Through comparative textual analysis, this study examines the fundamental differences between the Zahiri methodology and the majority school of jurists in interpreting Islamic evidence related to prayer procedures. The research findings indicate that while the majority school of thought uses a contextual approach and analogical reasoning (qiyās), the Zahiri school consistently adheres to the literal meaning of the text and rejects interpretations beyond the literal meaning. This study highlights the relevance of this methodological debate in contemporary Islamic jurisprudence discourse, particularly in addressing issues of worship not explicitly regulated in the texts. The study concludes that understanding this methodological comparison is crucial for enriching the literature on modern Islamic legal interpretation. Keywords: Perfection of the Rakaat, Textual methodology, Textual Literalism.